Linkage of national clinical datasets without patient identifiers using probabilistic methods. - Helen Blake; Linda Sharples; Katie Harron; Jan van der Meulen; Kate Walker (International Journal of Population Data Science, 2022)
Objectives To develop a step-by-step process for probabilistic linkage of national clinical and administrative datasets without personal information, providing guidance on selecting variables for linkage, estimating match weights, and choosing the probabilistic linkage threshold. To validate this process against deterministic linkage using patient identifiers.